Gas-chromatographic measurements of atmospheric CF2Cl2, CFCl3 and N2O from Tokyo to Syowa Station late in 1993, and at Syowa Station between February 1982 and January 1984 - Hirota, Michio; Makino, Yukio; Shiobara, Masataka; Chubachi, Shigeru; Muramatsu, Hisafumi (1985)
P(論文) Atmospheric CF_2Cl_2,CFCl_3 and N_2O were measured by a gaschromatographic method in order to assess the influence of these gases on the stratospheric ozone. Air samples were successively obtained by the 24th and 25th Japanese Antarctic Research Expeditions. From Tokyo to Syowa Station, volume mixing ratios of CF_2Cl_2 and CFCl_3 decreased toward the equator and were almost constant in the southern hemisphere. This is because most of CF_2Cl_2 and CFCl_3 have been released in the northern hemisphere. Volume mixing ratios of CF_2Cl_2 and CFCl_3 at Syowa Station as of January 1983 were lower by 6% than mean volume mixing ratios of them over Japan from October 1982 to February 1983. As for N_2O, no gradient in mixing ratio from Tokyo to Syowa Station was found. The mean value of total 19 samples was 302 ppb (=(10)^<-9>v/v). Over the period between February 1982 to January 1984,CF_2Cl_2 and CFCl_3 showed a steady increase at Syowa Station, and their annual increases were 19.2 ppt (=(10)^<-12>v/v)/year for CF_2Cl_2 and 10.2 ppt/year for CFCl_3. In the same period, N_2O was almost constant. departmental bulletin paper